PERENCANAAN PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI - Rudiarta, I Wayan (Guna Widya: Jurnal Pendidikan Hindu, 2024)
This research aims to conduct a critical analysis regarding the learning plans prepared by Pendidikan Agama Hindu dan Budi Pekerti teachers in implementing differentiated learning. The importance of this research refers to the phenomenon that the application of differentiated learning is still rarely carried out by teachers, including in the subjects of Hindu Religious Education and Character. This research uses a qualitative method where data collection is carried out by non-participant observation, structured interviews and documentation studies. Data analysis is carried out through data reduction, data display and conclusions. The results of the research found that in order to prepare a good differentiated learning plan, the things that need to be considered are related to the preparation of teaching modules, preparation of assessment instruments and preparation of essential material. The teaching module serves as a guide for teachers in carrying out learning activities from beginning to end, and in the context of differentiated learning, this teaching module can include designs for content differentiation, process differentiation, product differentiation and learning environment differentiation. Furthermore, the preparation of diagnostic assessment instruments is intended to map students based on learning readiness, interests and learning styles. Then the preparation of essential material is intended to support readiness for the process of achieving Learning Outcomes contained in the learning elements in the subjects of Pendidikan Agama Hindu dan Budi Pekerti.